A simple and quantitative ultrasonographic screening method for fetal Sylvian fissure abnormalities - Cuixia Guo; Lijuan Sun; Yan Liu; Tiejuan Zhang; Li Wang; Yuting Liang; Jingjing Wang; Qingqing Wu (European Journal of Medical Research)
Abstract Objective To explore a simple quantitative method for detecting fetal abnormal Sylvian fissure (SF) on ultrasonographic screening and to investigate its value in fetuses with SF abnormalities. Methods As the control group, 128 patients were examined prospectively by 2D ultrasound from 22 to 31 gestational weeks. We measured the depth of the SF (SFD) and width of the SF (SFW) and defined a new parameter, namely, the SF ratio (SFR), as the ratio of the SFW to the SFD. Reference equations were constructed for the SF parameters and gestational age (GA). Thirty-eight fetuses with SF abnormalities were included in the study group. Results In total, 310 ultrasound examinations were performed on 128 patients in the control group. The plateau-like insula was always present, and the SFD, SFW, and SFR increased with increasing gestational weeks between 22 and 31 gestational weeks. SFD (mm) = −1.48GA2−0.02GA+16.81 (R 2 = 0.803). SFW (mm) = 5.62GA2−0.08GA–79.34 (R 2 = 0.880). SFR = 0.53GA2−0.01GA-6.55 (R 2 = 0.619). The SFR was >0.7 from 22 to 24 gestational weeks and >1 after 25 gestational weeks in the control group. In the study group, the SFD, SFW, and SFR values were below the 5th percentile of the respective normal ranges in 26/38 (68.4%), 38/38 (100%), and 38/38 (100%) patients with abnormal SF. There were significant differences in three parameters between the two groups (P<0.05). With respect to the final diagnosis, 30/38 (78.9%) fetuses had malformations of cortical development (MCD), and 8/38 (21.1%) fetuses had multiple CNS malformations. Conclusions The SFR was >0.7 from 22-24 gestational weeks, and a value >1 after 25 weeks may serve as a simple parameter for detecting abnormal SF. An abnormal SF tends to be an indicator of CNS anomalies, especially MCD.